The Fetus Can Teach Us: Oxygen and the Pulmonary Vasculature - Payam Vali; Satyan Lakshminrusimha (MDPI AG, 2017)
Neonates suffering from pulmonary hypertension of the newborn (PPHN) continue to represent an important proportion of patients requiring intensive neonatal care, and have an increased risk of morbidity and mortality. The human fetus has evolved to maintain a high pulmonary vascular resistance (PVR) in utero to allow the majority of the fetal circulation to bypass the lungs, which do not participate in gas exchange, towards the low resistance placenta. At birth, oxygen plays a major role in decreasing PVR to enhance pulmonary blood flow and establish the lungs as the organ of gas exchange. The failure of PVR to fall following birth results in PPHN, and oxygen remains the mainstay therapeutic intervention in the management of PPHN. Knowledge gaps on what constitutes the optimal oxygenation target leads to a wide variation in practices, and often leads to excessive oxygen use. Owing to the risk of oxygen toxicity, avoiding hyperoxemia is as important as avoiding hypoxemia in the management of PPHN. Current evidence supports maintaining arterial oxygen tension in the range of 50-80 mm Hg, and oxygen saturation between 90-97% in term infants with hypoxemic respiratory failure. Clinical studies evaluating the optimal oxygenation in the treatment of PPHN will be enthusiastically awaited.